THE DIALOGUE OF CULTURES AND CIVILIZATIONS AS A FACTOR OF ENSURING WORLD ORDER AND CULTURAL INTEGRITY - Valentina Evgenievna Chernikova (Гуманитарные и юридические исследования)
The author examines the probem of cultural interaction as a factor of ensuring cultural stability. Russia is presented as a specific socio-cultural type within the frame of which the synthesis of western and oriental cultures is possible. As a result, a new integral civilizational type can be created.